Relationship between Contraception Selection and Number of Children, Perceptions of Side Effects and Perceptions of Information from the Community on Fertile Age Couples (PUS) in the Work Area of the Lubuk Buaya Community Health Center,Lubuk Buaya Village - Sandra Ilona (Science Midwifery, 2021)
The Family Planning Program (KB) is one of the programs used to address population increases. The purpose of the Family Planning Program (KB) is to improve the quality of the population through birth control, reducing mortality and increasing the quality of the family planning program, one of which is by implementing the Long-Term Contraception Method (MKJP). The purpose of this study was to analyze the relationship between contraceptive selection and the number of children, perceptions of side effects and perceptions of information from the community on fertile age couples in the work area of ​​Puskemas Lubuk Buaya, Lubuk Buaya Village, Padang City. This study used a cross sectional design. The study population was all fertile aged couples who were in the working area of ​​the Puskesmas, Lubuk Buaya Village, Padang City who received contraceptive services. The sample of this research is 108 respondents of fertile age couples who have received family planning services. Data collection using questionnaires and data analysis using chi-square test and logistic regression test. The conclusion of this study is that there is a relationship between the number of children, the perception of side effects and there is no relationship between perceptions of information from the community on couples of reproductive age and the choice of contraception.